EFFECTS OF JERUSALEM ARTICHOKE (HELIANTHUS TUBEROSUS.) PURAE ADDITION ON PHYSICAL CHARACTERISTICS AND SENSORY ACCEPTANCE OF MILK ICE CREAM - Bulan, Dusit; Paekul, Natcharat; Phuksuksakul, Apinya; Kumchoo, Sakuntra (Srinakharinwirot University Journal of Sciences and Technology, 2022)
The objective of this research aimed to study the effects of added Jerusalem artichoke puree at different concentrations including 0%, 10%, 20%, and 30% on physical characteristics and sensory acceptance of milk ice cream. Duncan’s New Multiple Range Test was used for comparing means in an analysis of variance at 95% confidence level. The study results showed that the addition of Jerusalem artichoke puree in milk ice cream tended to change characteristics of milk ice cream in accordance with characteristic enhancement with regard to appearance, smell, taste, texture, and overall preference, statistically significant (p<0.05) but color characteristic was not statistically significant (p>0.05). Jerusalem artichoke puree could be added at 20%. Testers accepted Jerusalem artichoke ice cream at a moderate level of preference. The addition of more Jerusalem artichoke puree to ice cream resulted in an increase in viscosity value, firmness value, and melting rate, and a decrease in overrun value compared to the control recipe. L* and b* values increased whie a* value decreased with an increase in the addition of Jerusalem artichoke puree (p<0.05). The recipe of Jerusalem artichoke puree ice cream included 12.96 Jerusalem artichoke puree, 49.46% fresh milk, 18.55% whipping cream, 3.09% milk powder, 15.45% sugar, 0.19% stabilizer, and 0.31% gelatin.